Research on Face Recognition and Privacy in China—Based on Social Cognition and Cultural Psychology - Liu, Tao; Yang, Bijiao; Geng, Yanan; Du, Sumin (Frontiers in Psychology, 2021)
With the development of big data technology, privacy has become the most critical social issue in the era of information sharing. In this paper, based on the perceived ease of use and perceived usefulness, a research model is built according to the privacy psychology, social cognitive, cultural psychology and influencing factors of face recognition users. An empirical analysis is carried out by using the questionnaire survey, and the structural equation model is adopted to explain the influence mechanism of the actual use of face recognition and privacy paradox so as to demonstrate the positive impact of perceived usefulness and trust on the use of face recognition, thereby providing recommendations for the development of the application of face recognition.